The right to oral hearing in disciplinary proceedings against public servants: position in Malaysia and the United Kingdom - Zukiferee, Ibrahim; Abdul Majid Tahir, Mohamed (2018)
The decision of disciplinary authorities in disciplinary proceedings continues to be judicially reviewed on the ground of its failure to grant oral hearing to the affected public servant albeit the well-established principle by the Privy Council in a Malaysian appeal of a Najar Singh 's case in 1976. Such failure will implicate the deliverance of justice and might affect the reputation and goodwill of Malaysian government as the major employer in the nation. Constitutional protection of reasonable opportunity of being heard to public servants under Article 135(2) in case of dismissal and reduction on rank should be interpreted in the light of fundamental right to life as enshrined in the Federal Constitution. Meanwhile, the application of the rule of natural justice on the right to be heard in an administrative action in the UK has embarked progressively with the decision of the House of Lords in a landmark case, Ridge v. Baldwin in 1964. The purpose of this article is to examine the regulation and policy in both countries on the application of right to oral hearing in disciplinary proceedings against their public servants. This paper forwarded a submission that on the ground of procedural fairness, oral hearing should be applied in disciplinary proceedings against public servants.